2003
DOI: 10.1590/s0074-02762003000400022
|View full text |Cite
|
Sign up to set email alerts
|

Action of Trypanosoma rangeli in infections with virulent Trypanosoma cruzi populations

Abstract: In experimental murine infections with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
2
17
0
4
Order By: Relevance
“…These results, which agree with the findings of other studies, show that human infection with T. rangeli does not cause the production of enough cross-reacting antibodies to interfere with the serodiagnosis of Chagas' disease (13,14). However, this does not exclude the possibility that exposure to T. rangeli may elicit a particular humoral and/or cellular immune response that confers some degree of protection against subsequent infection with T. cruzi (11).…”
supporting
confidence: 89%
“…These results, which agree with the findings of other studies, show that human infection with T. rangeli does not cause the production of enough cross-reacting antibodies to interfere with the serodiagnosis of Chagas' disease (13,14). However, this does not exclude the possibility that exposure to T. rangeli may elicit a particular humoral and/or cellular immune response that confers some degree of protection against subsequent infection with T. cruzi (11).…”
supporting
confidence: 89%
“…A diferencia de T. cruzi, T. rangeli secreta copiosamente las sialidasas en el intestino de los vectores, lo cual podría afectar la microbiota bacteriana del insecto y generar un efecto patógeno para el vector (Stoco, et al, 2014). Algunos investigadores consideran que en las regiones donde T. rangeli coexiste con T. cruzi en los mismos vectores y vertebrados, las infecciones de T. rangeli podrían alterar el curso de la enfermedad de Chagas en los vertebrados (Paláu, et al, 2003), pues se ha observado que la vacunación de ratones, cobayos y perros con T. rangeli induce protección inmunitaria contra cepas virulentas de T. cruzi (Basso, et al, 2007;Basso, et al, 2008Basso, et al, , 2014, lo que abre nuevas perspectivas para el control de la enfermedad de Chagas en los reservorios domésticos y, probablemente, en los humanos.…”
Section: Conclusionesunclassified
“…Of special interest is the unclear role of T. rangeli on human infections. This trypanosome is considered totally benign (Cuba Cuba 1998, Guhl & Vallejo 2003 but with significant immunological consequences on T. cruzi infection (Zuñiga et al 1997, Palau et al 2003, Basso et al 2004. It is therefore necessary to update the information concerning human trypanosome infections in endemic regions from Panama.…”
mentioning
confidence: 99%
“…Some authors have suggested that a previous T. rangeli infection in vertebrate hosts may have favourable effects in the clinical outcome of T. cruzi infection (Zuñiga et al 1997, Palau et al 2003, Basso et al 2004. To what extent the high prevalence of T. rangeli infection could explain the milder clinical form and/or the low prevalence of Chagas disease observed in this region (Sousa & Johnson 1973) further needs to be investigated.…”
mentioning
confidence: 99%